DECISION SUPPORT SYSTEM PEMBERIAN BONUS TAHUNAN PADA KARYAWAN BERDASARKAN KINERJA KARYAWAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (STUDY KASUS : STMIK PRINGSEWU) - Zulkifli Zulkifli; Sarifuddin Sarifuddin (Jurnal TAM (Technology Acceptance Model), 2016)
Bonuses is one method that is widely used as a form of tribute to workers whose performance so far can be considered satisfactory by the company. So is the case with STMIK Pringsewu that rewards Her staff as a token of appreciation for its performance over the years. However, the annual bonus is only given to employees who are considered berprestasit. It required a decision support system (DSS) or decesion support system that can take into account all the criteria that support and to help facilitate the decision making process. This decision support system using Simple Additive Wighting (SAW). The issue of decision support is basically a form of election of the various alternative actions that may be selected include discipline or the number of absences in a year, length of employment, crafts, and work in a year that the process through specific mechanisms, in hopes of generating a best decision. Employees who got the votes of 100% working receive an annual bonus that is the departure of the hajj, work evaluation 87.5% earn an annual bonus that is the departure of Umrah, and the assessment work 75% earn an annual bonus that is the departure of the general allowance.